STATE ADMINISTRATION OF THE ELECTORAL PROCESS IN RUSSIAN FEDERATION - Chistoborodov (Revista Inclusiones, 2019)
The article analyzes the concept of state administration of the electoral process in the Russian Federation. Particular attention is paid primarily to state administration in general and, subsequently, the concept of state administration of the electoral process is formulated. The legal aspect of this phenomenon requires legal consolidation in the current legislation. The article focuses on the fact that state administration is carried out in the sociopolitical sphere. In particular, it is implemented within the framework of state administration of the electoral process. The author finds it possible to consolidate the concept of state administration of the electoral process in the scientific literature. The main contribution to the science of the study is that the findings can be taken into account as guidelines in lawmaking and law enforcement. The research results expand the body of scientific knowledge in the field of state administration in general and allow to formulate the concept of state administration of the electoral process, in particular